2010
DOI: 10.1039/c0jm00509f
|View full text |Cite
|
Sign up to set email alerts
|

A simple and scalable route to wafer-size patterned graphene

Abstract: Producing large-scale graphene films with controllable patterns is an essential component of graphene-based nanodevice fabrication. Current methods of graphene pattern preparation involve either high cost, low throughput patterning processes or sophisticated instruments, hindering their large-scale fabrication and practical applications. We report a simple, effective, and reproducible approach for patterning graphene films with controllable feature sizes and shapes. The patterns were generated using a versatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
103
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 32 publications
6
103
0
1
Order By: Relevance
“…33,39 The PFPA chemistry has been used to globally modify surfaces or to modify discrete areas by arraying techniques such as photomasking or printing devices. 40 …”
Section: Introductionmentioning
confidence: 99%
“…33,39 The PFPA chemistry has been used to globally modify surfaces or to modify discrete areas by arraying techniques such as photomasking or printing devices. 40 …”
Section: Introductionmentioning
confidence: 99%
“…Physisorption of chemical species on graphene would provide a facile way to alter its electronic properties 12 , however, covalent chemical modification shows a great advantage in achieving permanent stabilisation for long-term usage 13 . Previous attempts towards fundamental research on covalent functionalisation of graphene mainly involved the development of new modification strategies (for example, hydrogenation [14][15][16][17] , fluorination [18][19][20] , chlorination 21,22 , diazotization [23][24][25][26][27] and other cycloaddition reactions [28][29][30][31] ), covalent addition of edge and defects 27,32 , fabrication of chemical superlattices 26,33 and quantum effects in graphene modification 17,34 . Of the various significant research activities on graphene chemistry that have been conducted, nearly no work to date has been focused on the asymmetric chemistry of this ideal 2D atomic crystal via covalently attaching different functional groups on its two faces simultaneously.…”
mentioning
confidence: 99%
“…However, the chemical modifications toward the nano-carbon materials must be necessary to obtain the reactivity and solubility, and the modifications cause the defection of the specific characteristics of the carbon materials. Yan et al suggested that perfluorophenyl azide (PFPA) is effectively worked for the immobilization of the carbon materials [27][28][29][30][31] and we also reported the immobilization of C 60 -fullerene (C60) on the surface of a silica monolith [32][33][34]. Additionally, we recently reported similar silica-monolithic capillary modified with C 70 -fullerene (C70), which has aspheric structure and greater π electrons compared to C60 [35][36][37], for the separation medium in LC [38].…”
Section: Introductionmentioning
confidence: 86%